Green consumption in Portugal : exploring the profile of green cosmetics' consumers - Soares, Ana Miguel Ribeiro Mortágua (2023)
The imperative for sustainable development has intensified in recent times leading to an increasing consumer demand for environmentally friendly cosmetics. This Master's Thesis explored the profile of green cosmetics consumers in the Portuguese market using the Theory of Consumption Values. It also identified barriers to the use of green cosmetics and investigated strategies to promote their purchase. This research employed an exploratory approach with methodological triangulation. A focus group (8 participants) and an online questionnaire (326 participants) were conducted. The study findings revealed the GC’ consumer in the Portuguese market gives priority to consumption values in the following order: functional - quality value; epistemic value; conditional value; emotional value; and functional - price value. Notably, social value emerges as the consumption value with the lowest level of importance. Consumers, in general, demonstrate environmental concern and values. Additionally, the study identified five distinct consumer segments based on the relative importance of consumption values, environmental concern level, and strength of environmental values. The focus group discussion shed light on various factors contributing to consumer reluctance in using GC. Participants identified factors such as insufficient environmental and financial literacy, perceived high prices, low societal value attributed to these products, lack of government support and incentives, inadequate and limited advertising efforts, certain product characteristics, and limited availability of scientific articles about this topic. Regarding strategies to enhance the consumption of GC, participants emphasized the importance of media engagement, involvement of authority figures, including governmental entities and effective brand communication through online platforms and outdoor advertising. This study aimed to enhance understanding of green consumption behaviour and segmentation, providing insights for industry stakeholders and recommendations for public authorities. However, the non-representative sample limits the generalizability of the findings, emphasizing the need for cautious interpretation.